A Novel Histological Technique to Assess Severity of Traumatic Brain Injury in Rodents: Comparisons to Neuroimaging and Neurological Outcomes - Frank, Dmitry; Gruenbaum, Benjamin F.; Shelef, Ilan; Zvenigorodsky, Vladislav; Benjamin, Yair; Shapoval, Olha; Gal, Ron; Zlotnik, Alexander; Melamed, Israel; Boyko, Matthew (Frontiers in Neuroscience, 2021)
Here we evaluate an alternative protocol to histologically examine blood-brain barrier (BBB) breakdown, brain edema, and lesion volume following traumatic brain injury (TBI) in the same set of rodent brain samples. We further compare this novel histological technique to measurements determined by magnetic resonance imaging (MRI) and a neurological severity score (NSS). Sixty-six rats were randomly assigned to a sham-operated, mild TBI, moderate TBI, or severe TBI group. 48 hours after TBI, NSS, MRI and histological techniques were performed to measure TBI severity outcome. Both the histological and MRI techniques were able to detect measurements of severity outcome, but histologically-determined outcomes were more sensitive. The two most sensitive techniques for determining the degree of injury following TBI were NSS and histologically-determined BBB breakdown. Our results demonstrate that BBB breakdown, brain edema, and lesion volume following TBI can be accurately measured by histological evaluation of the same set of brain samples.